If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3n = 19 Solving 7 + 3n = 19 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3n = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 3n = 19 + -7 3n = 19 + -7 Combine like terms: 19 + -7 = 12 3n = 12 Divide each side by '3'. n = 4 Simplifying n = 4
| 2y-6=5x+8 | | 9(r+8)= | | 24=x-36 | | 3t+9t=-110 | | 2x+x-6=90 | | 8+2n=4(5n) | | 4(6a-9)= | | 6.6x-5+x-1.7= | | -3+x=6 | | 3n-31=2 | | 3x-2x+9=6 | | 3(x-4)+5=x-15 | | 10-6n=-14 | | -3*x=6 | | y=-10/5+1 | | 10-6n=-4 | | m^4-5m^3+7m^2-3m=0 | | 6-(4x-2)=3-5x | | 2xy-xz=0 | | x+(-3)=-14 | | 2x^2-28x-64=0 | | 3x+5x=7x+9 | | -6+7x=0 | | 10y+6=8y-8 | | ln(-6+7x)=0 | | 3x^2+13x+22=0 | | 3(2a+15)-8a=-11 | | 6x-6=4x+42 | | 3(x+3)=-15 | | 50x^3+175x^2-8x-28=0 | | 45-2x=x+30 | | mn+16=4 |